Phenolic Composition, Antioxidant and Antimicrobial Activity of Cotoneaster Medik. Species from Bosnia and Herzegovina - Mahmutović-Dizdarević, Irma; Dizdar, Muamer; Čulum, Dušan; Vidic, Danijela; Dahija, Sabina; Jerković-Mujkić, Anesa; Bešta-Gajević, Renata (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2020)
Although the genus Cotoneaster Medik. includes mainly ornamental species, there are some data regarding its biological activity. The purpose of this study was to analyze the content of phenolic compounds, acetylcholinesterase inhibition, antioxidant and antimicrobial activity of methanolic extracts of leaf and bark of C. integerrimus Medik., C. tomentosus (Aiton) Lindl. and C. horizontalis Decne. The C. tomentosus leaf extract exhibited the highest content of total phenols (135.86 mg GAE/g) and flavonoids (18.17 mgQE/g), and also the most potent antioxidant activity against nonbiogenic free radicals, while the highest inhibition of acetylcholinesterase had the leaf extract of C. horizontalis (IC50 0.34 mg/mL). All extracts showed a significant level of antibacterial and antifungal activity against tested microbial strains. The largest inhibition zones were observed against Candida albicans treated with C. integerrimus leaf extract (30.50±0.50 mm). Furthermore, C. integerrimus extract was the most effective in the majority of bacterial strains tested. The results indicated that methanolic extracts of the investigated Cotoneaster species have promising bioactive and therapeutic potentials.